Ground. - Burke, Harry; Mul, Marlie ([s.l.] : [s.n.], 2018)
The Gate; Stupart, Linda ; Glow, Beatrice ; Wicker, Jean-Michel ; Barokka, Khairani ; Rodriguez, Shellyne
Ground is a zine that looks beyond institutions in their current form as dominant frameworks in artistic production, and embraces grassroots political and aesthetic perspectives.
boek